Impoliteness Strategy In K-Pop Song Lyrics By Blackpink: - - Samosir, Monalisa Br; Sembiring, Rony Arahta; Sihite, Jubilezer (Universitas Muhammadiyah Gresik, 2025)
This research aims to find out the types of impoliteness strategy and to find out the application of impoliteness strategy in the song lyrics. Blackpink. The data presented is 34 lyrics. This research is a qualitative descriptive research. The data source was taken from YouTube, totaling 13 songs. Data were analyzed based on the incivility strategy developed by Culpeper (1996). Types of impoliteness found in blackpink song lyrics, 1. Bald impoliteness when recorded 12% 2. Positive politeness 29% 3. Negative impoliteness 53% 4. Sarcastic or mocking politeness 6% 5. Withholding politeness 0%. Why here I don't find wiyhold impoliteness because in the song withhold impoliteness it is very rarely used. Culpeper (2005) makes two observations in the realm of impoliteness. First, he believes that language and non-linguistic cues do not imply impoliteness. To put it another way, neither language nor non-linguistic cues are inherently disrespectful but according to Culpeper (1996), impoliteness can be conveyed not only vocally but also non-verbally, such as avoiding eye contact. When assessing impoliteness, it is also necessary to examine paralinguistic and nonverbal aspects, which is why it is impossible to use this type of song. This finding shows that Blackpink's lyrics use more negative types of impoliteness, which is why the impoliteness strategy is suitable for use in this research.